STRATEGI PENINGKATAN KUALITAS PELAYANAN SIM CAK BHABIN DI POLRESTABES KOTA SURABAYA - Susi Ratnawati; Tri Prasetijowati; Fionita Eka Putri (Wacana Publik, 2023)
Making and extending a driver's license is one of the common needs of the Indonesian people, especially motorists. Based on this, the Polrestabes created a Mobile SIM innovation called "Cak Bhabin's SIM" for the extension and creation of a new SIM that can be reached by the public by increasing the number of locations for the "Cak Bhabin" SIM. Problems arise due to dissatisfaction from the community, namely regarding inadequate seating facilities, lack of socialization regarding daily service schedules and quotas, and often the E-AVIS application is not connected to the National Police Traffic Corps. The purpose of this study was to find out how to improve the service quality of SIM "Cak Bhabin" Surabaya City Police in dealing with some of these problems and the factors that influence service quality improvement. This study uses a qualitative descriptive analysis method with primary data as the main reference. Collecting the data by conducting interviews and documentation methods. The results showed that the factors influencing the improvement of the service quality for "Cak Bhabin" SIM services included the number of locations for "Cak Bhabin" SIM service locations spread over 24 location points in each sub- district in Surabaya, facilities and infrastructure that were in accordance with Law Number 25 Year 2009, the creation of the Korlantas Digital application intended for online SIM extension and the creation of the E-AVIS application for making a new SIM, as well as schedules, requirements, fees, systems/mechanisms and service procedures which can be viewed on the internet.